Creating Structural Defects of Drug‐Free Copper‐Containing Layered Double Hydroxide Nanoparticles to Synergize Photothermal/Photodynamic/Chemodynamic Cancer Therapy. Issue 2 (17th November 2020) - Sun, Luyao; Wang, Jingjing; Liu, Jianping; Li, Li; Xu, Zhi Ping
Abstract : Combination therapy has been extensively studied to achieve a more efficient inhibition of tumor progression. Herein, a nanoplatform based on layered double hydroxide (LDH) nanoparticles (NPs) is specifically constructed for the effective combination breast cancer therapy without the traditional anticancer drug. Cu‐containing LDH NPs loaded with indocyanine green (ICG) are devised with more Cu coordination defects (d‐Cu‐LDH/ICG) to induce photothermal/photodynamic/chemodynamic therapy (PTT/PDT/CDT) using only one laser source. The structurally created defects on the LDH surface and dual‐function ICG molecules in the LDH interlayer significantly enhance photothermal transduction and singlet‐oxygen ( 1 O2 ) generation at 808 nm laser irradiation. Moreover, d‐Cu‐LDH/ICG NPs generate hydroxyl radicals (·OH) in the presence of H2 O2 as Fenton catalysts, which are further enhanced by Cu(II) reduction with glutathione and temperature elevation. Consequently, d‐Cu‐LDH/ICG NPs significantly suppress 4T1 cell proliferation and show effective inhibition of the tumor growth in vivo through only one combined PTT/PDT/CDT under very mild laser irradiation, i.e., at 0.23 W cm −2 for 5 min with very low doses of Cu and ICG (2.5 and 0.5 mg kg −1 ). Altogether, the defect‐created d‐Cu‐LDH/ICG nanoplatform offers a new and safe treatment option for combination cancer therapy without using any anticancer drugs. Abstract : A defective copper‐containing layered double hydroxide nanoplatform loaded with ICG is devised with three fascinating features—vacancy‐facilitated photothermal transduction, enhanced ROS generation, and efficient GSH consumption. Combination treatment significantly inhibits 4T1 tumor growth in vivo under very mild laser irradiation. This drug‐free nanoplatform provides a new and safe treatment for breast cancer therapy.